2018
DOI: 10.1177/0361198118792338
|View full text |Cite
|
Sign up to set email alerts
|

Annual Average Nonmotorized Traffic Estimates from Manual Counts: Quantifying Error

Abstract: Across the United States, jurisdictions are investing more in bicycle and pedestrian infrastructure, which can benefit from nonmotorized traffic volume data. The design of nonmotorized counting programs varies. Whereas some agencies use automated counters to collect continuous and short duration counts, the most common type of bicycle and pedestrian counting is manual counting either in the field or from video. The objective of this research is to identify the optimal times of day to conduct manual counts for … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 9 publications
0
4
0
Order By: Relevance
“…Research on monitoring active transportation modes such as bicycling has supported advancements in practice, including reference-quality counts using permanent traffic recorders (6,7), and new approaches to crowdsource bicycling activity in addition to passive sensing using smartphones and other digital devices (8,9). Advancements in different approaches to bicycle counting support performance monitoring, including the critical challenge of comparing collision risk.…”
Section: Literature Review and Importance Of Researchmentioning
confidence: 99%
“…Research on monitoring active transportation modes such as bicycling has supported advancements in practice, including reference-quality counts using permanent traffic recorders (6,7), and new approaches to crowdsource bicycling activity in addition to passive sensing using smartphones and other digital devices (8,9). Advancements in different approaches to bicycle counting support performance monitoring, including the critical challenge of comparing collision risk.…”
Section: Literature Review and Importance Of Researchmentioning
confidence: 99%
“…Extrapolation has been used in several studies Journal of Advanced Transportation 3 for estimating Annual Average Daily Pedestrian (AADP) and Annual Average Daily Bicyclist (AADB) [4,6,25,44,45]. When collecting short-term counts, several factors such as counting period length, time of day, month, and year could potentially impact the accuracy of yearly count estimation [3,4,6,[45][46][47]. In addition to collecting short-term data, long-term count data at several locations are also required to perform the extrapolation.…”
Section: Short-term and Long-term Datamentioning
confidence: 99%
“…Due to limited resources and time, it is not possible to collect data for a whole year at many locations. Thus, a common practice is to collect short-term counts at several locations and apply an extrapolation method to convert short-term counts into yearly counts [3][4][5][6][7][8][9], which can be expressed in AADP or AADB forms. Exposure modeling can then be applied to estimate AADP or AADB for all other locations that were not originally selected.…”
Section: Introductionmentioning
confidence: 99%
“…4-1). Furthermore, [7] indicated that the most common source for pedestrian data is manual counts, even though annual estimates from shortterm manual counts could generate errors between 30 and 60 percent. Additionally, [8] indicate that the research related to the study of temporal factors for non-motorized traffic is scarce.…”
Section: Introductionmentioning
confidence: 99%